(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate serum pepsinogen levels and their associations with histopathological features in patients with chronic gastritis and Helicobacter pylori infection. Subject and methods: This analytical cross-sectional study included 59 patients with chronic gastritis and H.pylori infection at 30-4 Hospital from June 2025 to January 2026. Serum pepsinogen I and pepsinogen II levels were measured by ELISA and the pepsinogen I/II ratio was calculated. These indices were compared according to the degree of mucosal damage, inflammatory activity and intestinal metaplasia. Results: The mean age of the patients was 46.1 ± 16.4 years, and 52.5% were female. The median serum pepsinogen I level, serum pepsinogen II level, and pepsinogen I/II ratio were 66.7 ng/ml, 18.9 ng/ml and 3.5, respectively. The pepsinogen I/II ratio was significantly lower in patients with active gastritis and those with intestinal metaplasia. No statistically significant differences were observed in serum pepsinogen I or pepsinogen II levels across histopathological features. The pepsinogen I/II ratio showed discriminatory ability for active gastritis and intestinal metaplasia, with areas under the curve of 0.85 and 0.723, respectively. Conclusion: The pepsinogen I/II ratio may serve as a noninvasive serum biomarker for assessing inflammatory activity and precancerous gastric lesions in patients with chronic gastritis and H.pylori infection.